PERTUMBUHAN DAN PRODUKSI TANAMAN SORGUM (Sorghum bicolor L.) DENGAN PEMBERIAN BEBERAPA KOMBINASI KOMPOS DAN PUPUK P - Nanda Selvia; Arifien Mansyoer; Jurnawaty Sjofjan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This study aimed to examine the effect of compost TKKS combined with green manure and the addition of P fertilizer on the growth and production of sorghum and get the best dose. Research conducted experimentally using factorial randomized block design consisting of two factors (a combination of compost and manure P) and 3 replications. Data were analyzed statistically using ANOVA using Duncan's test New Multiple Range Test (DNMRT) mean separation 5%. The results showed that treatment with compost fertilizer P had not significantly effect on plant height, stem diameter, leaf length, panicle stalk length, number of branches per panicle, seed weight per panicle, production per plot, 100 seeds weight but significantly affect on flowering. Organic fertilizer at 266.67 kg/ha in combination TKKS 50% + 50% LCC and fertilizer P 86.67 kg/ha SP-36 gave the best effect to the acquisition results in the production of seed weight per plot was 2092.9 g / plot, higher compared to 100% + 0% TKKS compost and fertilizer P LCC 31.21 kg / ha SP 36.   Keywords: Compost TKKS, green manure, fertilizer P and Sorghum (Sorghum bicolor L.)